Las creencias del aprendiz tardío en relación al aprendizaje del idioma inglés: el caso de los estudiantes de maestría y doctorado de la Universidad Nacional de Trujillo - 2008 - Tantaleán Smith, Consuelo (2012)
The main objective of this study was to describe the beliefs system concerning the learning of the English language in late learners. At the same time, we intended to identify the communication needs and preferences with regard to the learning of English as a Foreign Language. The beliefs of the late learners in relation to the learning of the English language in a sample of sixty-five students who belonged to a population of two hundred candidates of Master’s and Doctor’s Degrees of the National University of Trujillo were evaluated. Horwitz’s questionnaire (1988) was adapted to collect information about beliefs of learning and an individual questionnaire (García-Romeau, 2006) was used for the analysis of students ‘needs. The learner’s system of beliefs about second language learning ( Horwitz 1988) was divided into four themes (1) Foreign language aptitude, it is easier for children than adults to learn a foreign language; (2) Difficulty of language learning, everyone can learn to speak a foreign language and some languages are easier to learn than others; (3) Nature of language learning, it is important to repeat and practice often; (4)Learning and communication strategies, it is important to speak a foreign language with an excellent accent. Furthermore, the results indicated the following hierarchy of competences: 1st Reading, 2nd Listening, 3rd Writing and 4th Speaking. The favorite learning style was the auditory one